Prevalence of bovine norovirus and nebovirus and risk factors for infection in Swedish dairy herds - Tråven, Madeleine; Axén, Charlotte (Swedish University of Agricultural Sciences, 2022)
Aim of the study was to determine the prevalence of bovine norovirus and nebovirus infections in dairy calves in Sweden. A secondary aim was to analyse herd and management factors associated with these infections. In this study, samples and data collected for another study in 2005-2007 were used (Silverlås et al. 2009. Prev. Vet. Med. 90, 242-253). The samples and data were originally collected for studying Cryptosporidium infections. Fecal samples from 5 calves 2-30 days of age were collected by a veterinarian visiting each farm once, in total 50 farms. For the present study, samples were analysed by RT-PCR for bovine norovirus and nebovirus. For specification of the methods, see the published paper. The management data were collected at the farm visits by observation and interview of farmers using a standardized questionnaire.

The dataset contains the results of RT-PCR analyses of fecal samples from young calves for bovine norovirus and nebovirus. Five calves per herd in 50 Swedish dairy herds were included in the study. The dataset also includes information about the herd, i.e. herd size, average yearly production and a number of variables concerning management of calvings and calves. Such management routines could influence the level of calf health and transmission of infections. These data were gathered through standardized interviews with the farmers. Data compiled in two separate files, calf level data (individual), 250 rows + heading, herd level data, 50 rows + heading.

Studiens syfte var att bestämma prevalensen för bovint norovirus och nebovirus hos kalvar i svenska mjölkkobesättningar. Ett andra syfte var att analysera besättnings- och skötselfaktorer associerade med dessa infektioner. I studien användes prover och data insamlade i en tidigare studie 2005-2007 (Silverlås et al. 2009. Prev. Vet. Med. 90, 242-253). Prover och data samlades ursprungligen in för att studera cryptosporidieinfektioner. Träckprover från 5 kalvar 2-30 dagar gamla togs av veterinär vid ett besök på varje gård, totalt 50 gårdar. För den här studien analyserades proverna med RT-PCR för bovint norovirus och nebovirus. För mer information om metoderna, se den publicerade artikeln. Skötsel- och besättningsdata samlades in vid besättningsbesöket genom observationer och intervju av lantbrukaren via ett standardiserat frågeformulär.

Datasetet innehåller analyssvar från RT-PCR för bovint norovirus och nebovirus i träckprover från 5 unga kalvar /besättning i 50 svenska mjölkkobesättningar. Datasetet innehåller också uppgifter om besättningarna, såsom besättningsstorlek, årlig medelproduktion och ett antal variabler som beskriver rutiner runt skötsel av kalvningar och kalvar, vilka kan ha betydelse för kalvhälsan och smittspridning. Dessa data har samlats in via ett standardiserat intervjuformulär. Data uppdelade på två filer, data på kalvnivå (individ), 250 rader + rubrik, data på besättningsnivå, 50 rader + rubrik.
Bovina norovirus och nebovirus - prevalens och riskfaktorer för infektion i svenska mjölkkobesättningar
Keywords: Cattle Diseases; Nötkreatursjukdomar; Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; calves (bovine); kalvar (nötdjur); colostrum; råmjölk; risk factors; riskfaktorer; diarrhea; diarré; bovine norovirus; bovint norovirus; RT-PCR; RT-PCR; nebovirus; nebovirus; calf health; kalvhälsa; dairy herds; mjölkkobesättningar; management routines; skötselrutiner; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Plants and animals; Växter och djur; Agriculture and rural industry; Jordbruk och landsbygdsnäring; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Clinical Science; Klinisk vetenskap; Farming; Areella näringar; Other Veterinary Science; Annan veterinärmedicin